Integration of Microhydro Power Plant with Internet-Based Monitoring System for Energy Independent Villages - Sujadi, Harun; Koswara, Engkos; Mardina, Ardi; Abdullah, Fatwa Muhammad Maulid; Subandi, Dipa (Pascasarjana Universitas Mataram, 2025)
This community service activity aims to integrate Internet of Things (IoT) technology into the monitoring system of a Microhydro Power Plant (PLTMH) in Argamukti Village, Majalengka Regency. The village has significant renewable energy potential, but challenges in real-time energy production monitoring have hindered the plant's optimal performance. By implementing an IoT-based monitoring system, the operational efficiency of the PLTMH can be significantly improved. This program includes training in IoT device installation and guidance for local communities in operating and maintaining the system. The results show a 20% increase in energy production efficiency compared to the period before the monitoring system was implemented. Furthermore, the local community is empowered to manage energy resources independently, supporting the establishment of Energy Self-Sufficient Villages. This initiative aligns with government efforts to promote renewable energy usage in rural areas. The IoT technology implementation also opens opportunities for applications in other sectors such as smart farming and water management, which can sustainably enhance the local community's welfare.